Problem Based Learning (PBL) Berorientasi Higher Order Thinking Skills (HOTS) Untuk Meningkatkan Hasil Belajar IPS - Muhammad Farhan; Risma Dwi Arisona (Pendidikan IPS FKIP ULM, 2022)
The conventional Social Education learning process at SMPN 2 Ponorogo resulted in students not being interested in participating in learning activities. As a result, student learning outcomes are low, and students inability to think at higher levels. This study aims to (1) determine the application of PBL (Problem Based Learning) learning oriented to HOTS for Social subjects in class VII C SMPN 2 Ponorogo (2) find out the improvement of Social Education learning outcomes in class VIII C SMPN 2 PONOROGO using the PBL (Problem Based Learning) oriented to HOTS (Higher Other Thinking skills). This study used the Class Action Research model by Kemmis and Mc. Taggart, which consists of two cycles. The subjects of this study consisted of 32 students of class VIII C SMPN 2 Ponorogo. The results showed that (1) the application of the Problem Based Learning (PBL) learning model oriented to Higher Other Thinking Skills (HOTS) contained three activities, namely: initial, core, and closing. The teacher sets the cognitive domain C4 (Analyzing) as the observed Higher Other Thinking Skill (HOTS). The results from cycle I to cycle II on the ability of C4 (analyzing) with categories of distinguishing, organizing, and attributing there was an increase. (2) There was an increase in learning outcomes in the second cycle of students who completed by 87%. The Problem Based Learning (PBL) learning model oriented to Higher Other Thinking Skills (HOTS) improved Social Education learning outcomes.Keywords: Problem Based Learning, Higher Order Thinking Skills, learning outcomes, social studies education learning